Numerical Study of Solid Oxide Fuel Cell Contacting Mechanics. Issue 1 (2nd February 2018) - Chen, Z.; Wang, X.; Brandon, N.; Atkinson, A.
Abstract: Assembly of a planar solid oxide fuel cell (SOFC) or solid electrolyzer (SOE) stack involves the lamination of cells and interconnect plates under an applied load. In most designs a pattern of ribs on the interconnector makes contact with a porous ceramic current collector layer on the air side. These localized contacts are regions of increased stress on the cells and can cause damage if the stresses become too large. In this paper the mechanical response of an anode‐supported cell to localized loads from interconnector ribs is simulated. The simulations show that the critical stress for initiating and propagating a crack in the electrolyte (∼300MPa for a 10 μm thick electrolyte) is reached when the interconnector displacement reaches 20 μm (after touching the cathode) with reduced support, or 30 μm when in an oxidized state. The difference is due to the lower stiffness of the reduced support. The residual compressive stress in the electrolyte layer has a major protective effect for the electrolyte. It is concluded that fracture is very unlikely for a geometrically perfect contact, but if the contact is non‐uniform due to manufacturing variability in the contact plate or cell, local displacements >∼20 μm can be dangerous. The simulations are used in an example of contacting geometry optimization.